Promosi Kesehatan Berbasis Media Digital Di Rumah Sakit PKU Muhammadiyah Kartasura - Anggie Annisa Permatasari; Nannyk Widyaningrum; Ummu Muti 'ah; Nisa Nur Rahma (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
As information technology develops, the development of digital media has also shown its role in health promotion efforts. Health promotion is carried out through activities to provide information, influence and help the community to improve their health status. Currently, digital media is more dominantly used in health promotion activities. The use of various media to provide education, convey information and promote health really helps services to the community. So that people can more easily receive information quickly and accurately. This research aims to 1) the type of digital media used 2) the urgency of using digital media in health promotion efforts 3) the role of health promoters in carrying out health promotion based on digital media. In this case the solution offered to partners is to hold outreach regarding health promotion based on digital media in hospitals. The output target of this activity is that it is hoped that health workers will have knowledge in creating digital media-based health promotions in hospitals in more varied ways. In this service the author produced an article on digital media-based health promotion in hospitals